The Analysis of Chemistry Test Item Difficulty on XI MIPA Year-End Assessment at SMAN 8 Pontianak - Pitra Dewi; Hairida Hairida; Rahmat Rasmawan; Masriani Masriani; Tulus Junanto (Universitas Pendidikan Mandalika, 2023)
This study aims to categorize the level of difficulty of the questions and describe the cognitive level of the KKO indicators of the 2021/2022 year-end assessment (PAT) of chemistry class XI MIPA at SMAN 8 Pontianak. This research is quantitative descriptive. Data collection techniques were interviews and documentation. Documentation was obtained from chemistry teachers through google forms containing answers and PAT questions. The research subjects amounted to 150 students of class XI MIPA who had taken the End of Year Assessment. The results of the research obtained are difficult categories totaling 4 questions (13.3%), moderate 10 questions (33.3%) and easy 16 questions (53.4%). The results of the analysis obtained in order to improve the distribution of the difficulty level of questions in the future.